Condition states of the low plain grass pasture site present in the Loventué La Pampa department (Semiárida, 2020)
It has been evaluating range condition in twenty areas of shortgrasslands in Loventué - La Pampa. The state Condition's identification was realized with the standing - crop's dates. Frequency, density, cover and height of principal’s species were taken. The following indices were used to classified the grassland's Condition: Very Good; Good, Fair, Poor and Very Poor.
Keywords: Condition; Shortgrasslands; Uplands